Input to the lateral habenula from the basal ganglia is excitatory, aversive, and suppressed by serotonin - Shabel, Steven J. (2012)
The lateral habenula (LHb) has recently been identified as a key regulator of the reward system by driving inhibition onto dopaminergic neurons. However, the nature and potential modulation of the major input to the LHb originating from the basal ganglia are poorly understood. Although the output of the basal ganglia is thought to be primarily inhibitory, here we show that transmission from the basal ganglia to the LHb is excitatory, glutamatergic and suppressed by serotonin. Behaviorally, activation of this pathway is aversive, consistent with its role as an ‘anti-reward’ signal. Our demonstration of an excitatory projection from the basal ganglia to the LHb explains how LHb-projecting basal ganglia neurons can have similar encoding properties as LHb neurons themselves. Our results also provide a link between ‘anti-reward’ excitatory synapses and serotonin, a neuromodulator implicated in depression.